Pengembangan Aplikasi Permainan Pembelajaran Matematika menggunakan Model-Driven Game Development - Umair, Umair; Tawakal, Hilmy Abidzar (LPPM STT Terpadu Nurul Fikri, 2021)
Computer games empirically prove to complement metacognitive abilities that cannot obtain through ordinary mathematics education. Game-based learning also shows to increases engagement, motivation, critical thinking, and learning skills. However, the process of developing learning games requires collaboration with various parties who have different backgrounds. The model-driven development approach simplifies communication and collaboration between parties with different backgrounds because it uses a modeling language easily understood by various parties. The Usability Testing that the authors get by using a questionnaire states that this game's usability rate is 87.22%. The test also shows that educational games with the platformer genre can encourage players to learn.